Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 943 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Falco cherrug J.E.Gray, 1834", "HasCoordinate is true", "HasGeospatialIssue is false", "BasisOfRecord is Human Observation" ] } The dataset includes 943 records from 12 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0050779-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences